2016
DOI: 10.5897/err2015.2119
|View full text |Cite
|
Sign up to set email alerts
|

The use of cartoons in elementary classrooms: An analysis of teachers behavioral intention in terms of gender

Abstract: Among multimedia researches, contribution of cartoons to teaching process and academic achievement has often been examined. However, these technologies may have a slower and less effect since acceptance of them by users is affected by many factors. Therefore, it is extremely important to understand and reveal the factors which encourage teachers who are to choose the most appropriate tool and material for students during teaching period to use cartoons for teaching or restrict their use. To this end, teachers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
0
1
Order By: Relevance
“…On the other hand, studies by Milutinovic (2022), Akar (2019), Sahin and Ibilli (2016), Hong et al (2021), Kazoka andMwantimwa (2019), andJoo et al (2018) are also inconsistent with the present study, these previous studies found a combination of perceived usefulness and perceived Ease of use, together with external variables, directly influence teachers behavioural intentions in various learning contexts and the goal of the study. Furthermore, the present study is inconsistent with the original TAM on the role of perceived usefulness.…”
Section: Discussioncontrasting
confidence: 94%
“…On the other hand, studies by Milutinovic (2022), Akar (2019), Sahin and Ibilli (2016), Hong et al (2021), Kazoka andMwantimwa (2019), andJoo et al (2018) are also inconsistent with the present study, these previous studies found a combination of perceived usefulness and perceived Ease of use, together with external variables, directly influence teachers behavioural intentions in various learning contexts and the goal of the study. Furthermore, the present study is inconsistent with the original TAM on the role of perceived usefulness.…”
Section: Discussioncontrasting
confidence: 94%